Catalysis for renewables : from feedstock to energy production - Centi, Gabriele, 1955-; Van Santen, Rutger Anthony, 1945- (Weinheim : Wiley-VCH, 2007)
With its focus on catalysis and addressing two very hot and timely topics with significant implications for our future lives, this will be a white book in the field. The authority behind this practical work is the IDECAT Network of Excellence, and the authors here outline how the use of catalysis will promote the more extensive use of renewable feedstocks in chemical and energy production. They present the latest applications, their applicability and results, making this a ready reference for researchers and engineers working in catalysis, chemistry, and industrial processes wishing to analyze options, outlooks and opportunities in the field.
Includes bibliographical references and index.
Keywords: Biomass chemicals; Biomass energy; Biomassa; Catalysis; Duurzame energie; Energy crops; Renewable energy sources